"A social worker…teacher…principal – we're everybody": The School Police Officer Role in Schools. (2nd October 2022) - Debnam, Katrina; Camacho, Daniel; Henderson Smith, Lora; Bottiani, Jessika
ABSTRACT: The current study explored the experiences and activities of school resource officers (SROs) in an urban school district. Twenty-eight SROs completed a survey assessing their roles in schools and a focus group explored how the SROs build relationships with students and the types of student concerns they help resolve. Themes from the focus group included the SROs' attempts to navigate change in policies and procedures in the school system; the community contexts of the school system and its impact on SRO duties; and role ambiguity, including differences in how SROs perceived their roles within schools compared to how others saw them. Study findings call attention to underlying tensions between SROs and positive youth development in an era where SRO presence in schools is highly debated.